Data Politics At The Grassroots - Milan, Stefania; van der Velden, Lonneke (AoIR Selected Papers of Internet Research, 2017)
Novel forms of civic engagement and political action emerge in the age of datafication. Data activism indicates the series of social practices that at different levels, in different forms, and from different points of departure are concerned with a critical approach to big data, and massive data collection in particular. Data activists address massive data collection as both a challenge to individual rights, and a novel set of opportunities for social change. They appropriate technological innovation for political or social change purposes. This new empirical phenomenon emerges at the intersection of the social and technological dimensions of human action. It rises from the open-source and hacker movements, but overcomes their elitist character to increasingly involve ordinary users, thus signaling a change in perspective towards massive data collection emerging within civil society. It concerns both individuals and groups, and operates at different territorial levels, from local to transnational. Combining Social Movement Studies and Science and Technology Studies, this theoretical paper offers a conceptual map to approach grassroots engagement with data from an interdisciplinary perspective. It presents three ways of mobilizing the notion of data activism for research purposes: a) as a heuristic tool for empirical analysis and theoretical development, b) as a novel epistemic culture emerging within the realm of civil society, and c) as a theoretical device to rethinking citizenship in the datafied society.